Silvicultura en la Amazonia Peruana: diagnostico de experiencias en la region ucanyali y la provincia de Puerto Inca - Nalvarte, W.; Sabogal, C.; Galvan, O.; Marmillod, D.; Angulo, W.; Córdova, N.; Colan, V. (CIFOR, INAENA, INIA, Universidad Nacional de Ucayali, 2004)
The documented silvicultural experience in the Peruvian Amazon dates back several decades with methods such as enrichment plantings, open plantations, agroforestry systems and management of natural regeneration of some commercial timber species. However, much of the known experiences are barely documented and there is almost no systematization and analysis. This document describes the methodology, results and main conclusions and recommendations of a diagnostic study geared to improve the utilization of the wide silvicultural experience in the Peruvian Amazon with native species and to offer technical recommendations to improve the competitivity of silvicultural practices for the regeneration of residual, degraded and secondary forests. The study was geographically restricted to the Ucayali region and the province of Puerto Inca in the department of Huánuco, where over the past two decades a rich experience has accumulated with several silvicultural methods and practices, duly documented in the study. The silvicultural analysis was carried out on 31 sites with a total of 61 assessment units. The database produced includes 32 tree species with over 13 mil registers corresponding to 4861 living trees on 110 ha sampled out of over 800 ha evaluated. The results for those species with more consistent information is presented, which includes caoba (Swietenia macrophylla), cedro (Cedrela odorata), ishpingo (Amburana cearensis) and tornillo (Cedrelinga catenaeformis). Finally, the study arrives at several conclusions with implications and recommendations.